Utilization of Promotional Videos for Harum Badariak Barandang Peanuts in Pariangan Sub-district on YouTube Social Media. - Refika Mastanora; Andi Melta (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This community service is motivated by the suboptimal promotion of the barandang peanuts as an iconic product in Nagari Sawah Tangah, Pariangan Sub-district. Some identified problems include Production Challenges, Marketing Management, and Promotion. The Community Service Team focuses on utilizing promotional media through social media, particularly YouTube. The results obtained after creating promotional videos showed an increase in sales from 30 packages per day to 50 packages per day. It can be inferred that the utilization of videos is necessary to reach potential buyers both within and outside the region